The mediating effect of family support in the relationship between socio-economic status and postpartum depressive symptoms - Yuyin Xiao; Yujie Cui; Feifei Li; Wu Zeng; Scott Rozelle; Chenshu Shi; Jianing Xu; Jiaqi Shi; Guohong Li; Fan Jiang (BMC Public Health)
Abstract Background The aim of this study is to explore the mediation effect of family support on the relationship between SES and postpartum depressive symptoms. Methods A total of 1887 mothers of newborn babies under 6 months of age in selected community health service centers in Shanghai were included in the analysis. A multi-stage probability sampling method was applied to select the sample. We generated a composite index for measuring each sample household’s SES using a categorical principal component analysis approach. The mothers’ perceived family support scale was used to reflect family functioning status. Regression models were used to verify the research hypotheses and assess the impact of intermediating variables. Results 8.90% of participants had postpartum depressive status. The data showed that there was variability in the SES index, ranging from -4.18 to 0.81 (with lower SES being a low index value). According to the findings, the SES index was negative associated with depressive symptoms, the lower the SES level of the household, the higher the probability of the mother being at risk for depressive symptoms. (β = -0. 115, P < 0.001). When examining the analysis that adds family support as a mediator between SES and depressive symptoms, the coefficient of the mediator (family support) was significant (meaning the higher the family support, the lower the risk of depressive symptoms (β = -0.447, P < 0.001) and the coefficient relating the SES index to depressive symptoms became non-significant (β = -0.023, P = 0.280). Conclusion The association between SES and depressive symptoms among postpartum women is strongly mediated by family support. The finding suggests that the focus of interventions to prevent or mediate postpartum depression should consider developing strategies to strengthen family support.